Pembelajaran Matematika Materi Persamaan Garis Lurus dengan Model Guided Discovery Learning Berbantuan Geogebra - Muhammad Idris Septrianto; Jumadi Jumadi; Uki Suhendar (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2019)
This research aims to describe the results of the application of straight line equation learning with guided discovery learning model assisted by geogebra. This qualitative research took the subject is a class VIII student at MTs Muhammadiyah 1 Ponorogo. Data collection uses observation and documentation techniques. The data obtained were then analyzed descriptively. It was concluded that the application of straight line equation learning for students of class VIII of MTs Muhammadiyah 1 Ponorogo with a guided discovery learning model assisted by geogebra was carried out with the beginning of the Stimulation step, then the Problem statement, then the Data collection, followed by Data Processing, then Verification, ending with Generalization. Geogebra help is given during the stimulation and verification steps. The results of the application of this learning are student participation, confidence, and understanding increase. However, the teacher's guidance and creativity largely determine the successful implementation of the guided discovery learning model assisted by geogebra.